A New Deterministic Linear Network Coding and Its Application on Multicast Network - Kun Hao; Zhigang Jin (2009 5th International Conference on Wireless Communications, Networking and Mobile Computing, 2009)
Network coding is a promising technique to improve the resource efficiency and reliability for multicast networks. With network coding, each node of the multicast network is able to generate and transmit encoded data of information. This paper proposes a deterministic linear network coding scheme. This scheme exploits a special type of network topology called uniform network. This network structure is proved that it can achieve higher network coding gain with network coding. The scheme can accommodate dynamic membership and construct a much simple overlay network topology. The system performance is further improved, whether in throughput or in reliability. Our simulation results show that the new scheme can improve throughput, compared to the traditional multicast system, by at most 10% to 15%. Moreover, it achieves good reliability and robustness to dynamic peer arrival or leave.